2022
DOI: 10.1007/s00167-022-07174-1
|View full text |Cite
|
Sign up to set email alerts
|

No correlation between performance tests, clinical measurements and data from patient-reported outcome measures (PROM) in children reconstructed for anterior cruciate ligament injury

Abstract: Purpose To investigate if patient-reported outcome measures (PROMs), functional tests and clinical measures correlate well in children after reconstruction of the anterior cruciate ligament (ACL). It was hypothesized that these outcomes correlate, so it is suicient to report only one of them. Methods A consecutive group of children (< 16 years old) who had an ACL reconstruction, were prospectively followed and assessed after 1-year with Pedi-IKDC and KOOS-Child, instrumented laxity measurement, range of motion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…Therefore, one outcome is not representative for the condition, and the study hypothesis was rejected. The low correlations demonstrated in the current study are comparable to what has been found in children with ACL injury [ 33 ]. In a group of 75 athletes who were tested in relation to return to sport 9 months after ACLR there was a negligible correlation between limb symmetry index of single leg vertical jump height and IKDC score ( r = 0.26) [ 21 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Therefore, one outcome is not representative for the condition, and the study hypothesis was rejected. The low correlations demonstrated in the current study are comparable to what has been found in children with ACL injury [ 33 ]. In a group of 75 athletes who were tested in relation to return to sport 9 months after ACLR there was a negligible correlation between limb symmetry index of single leg vertical jump height and IKDC score ( r = 0.26) [ 21 ].…”
Section: Discussionsupporting
confidence: 87%
“…One tested the correlation between the limb symmetry index for the one-leg vertical jump test against the subjective IKDC scores ( r = 0.26), Tegner score ( r = 0.64) and the ACL-RSI (Return to Sport after Injury) scale scores ( r = 0.61) nine months after ACLR in younger, adult male athletes [ 21 ]. The other found that in children who had an ACLR 1 year earlier there were no clinically important correlations between scores obtained by Pedi-IKDC and KOOS-Child, laxity measures, knee muscle strength and four functional performance tests [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, a previous study also did not find a correlation between patient-reported functional outcomes and objectively measured strength. 26 Therefore, isokinetic strength may not have been an appropriate choice to assess the convergent validity of a psychological assessment questionnaire such as the ACL-RSI, as these are likely measuring different Age at return-to-sport testing and body mass index (BMI) were analyzed using Spearman correlation, sex was analyzed using Mann Whitney U test, and race and ethnicity were analyzed using Kruskal-Wallis test (N = 51). ACL-RSI, Anterior Cruciate Ligament-Return to Sport after Injury; N/A, not applicable.…”
Section: Discussionmentioning
confidence: 99%
“…However, a previous study also did not find a correlation between patient-reported functional outcomes and objectively measured strength. 26 Therefore, isokinetic strength may not have been an appropriate choice to assess the convergent validity of a psychological assessment questionnaire such as the ACL-RSI, as these are likely measuring different constructs altogether. Range of motion may have been a better choice as another study of the ACL-RSI in a young population (18 athletes aged 20 ± 7.4 years) found that range of motion of the hip and knee correlated with ACL-RSI score, with knee frontal plane range of motion being the most significant factor.…”
Section: Discussionmentioning
confidence: 99%
“…A significant factor for this is an increased participation in sports among children, compared to earlier. Additionally, there has been a tendency towards early specialisation and intensified sports training at an early age [14,26,31,38,45,46,48].…”
Section: Introductionmentioning
confidence: 99%